The factors affecting job satisfaction amongst employees: A case study of Eastern Pacific Industrial Corporation Berhad, Annexe Building, Pangkalan Bekalan Kemaman Sdn. Bhd. / Siti Nailah Che Aman - Che Aman, Siti Nailah (Bachelor of Science (Hons.) Statistics, 2015)
This quantitative research aims to further understand which of the factors betweeen working conditions, management performance and salary and benefits has the most influence in job satisfaction among employee at Pangkalan Bekalan Kemaman Sdn. Bhd. This includes the objectives as follows: (1) To identify the relationship between working condition, management performances and salary and benefits towards job satisfaction among employees. (2) To determine which factors that most contributes to job satisfaction among employees. (3) To examine how certain demographic variables (gender, educational qualifications, years of working and department) affect job satisfaction. Survey data was collected from a sample of 150 employees that randomly selected from eight strata’s which were selected through stratified sampling technique. Questionnaires were distributed among these employees in gathering data with based on working conditions, management performance, salary and benefits affecting their job satisfaction. Statistical Package for Social Science (SPSS) software, version 20.0 was used to analyze the data. The reliability test was conducted using Cronbach Alpha and data was analyzed using descriptive statistics such as frequency distribution and inferential statistics, namely Pearson Correlation, Multiple Regression, T-test Independent and One-Way ANOVA. The Pearson Correlation Analysis revealed that there is astrong and significant relationship between working conditions, management performance, and salary and benefits with job satisfaction (r = 0.846, r = 0.772 and r = 0.741). The R Square of 0.765 from Multiple Regression Analysis shows that 76.50% of job satisfaction can be explained by working conditions, management performance, and salary and benefits. The Multiple Regression Analysis also shows that working conditions and salary and benefits are the strongest predictors of job satisfaction with Beta Co-efficient 0.694 and 0.273. There are some recommendations which researcher may wish to recommend for the future research related in this field. The researcher suggests that future study can consider other factors such as job security, relation with Co-workers, and relation with supervisor